2017
DOI: 10.1037/cap0000095
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment or dependency? The religion/religiosity–mastery relationship.

Abstract: Whereas religion/religiosity (R/R) tends to have a positive relationship with psychological well-being in general, the relationship between R/R and Mastery is less clear. Research investigating R/R–mastery has reported a positive, nonsignificant, and negative relationship, and often uses informal composite measures to assess R/R without a substantive discussion surrounding their suitability. The current study used a national Canadian sample (N = 12,930) to investigate the moderating effect of socioeconomic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Firstly, the literature is loaded with agnosticism. It has shown that effects of religiosity on SOC are varying (i.e., sometimes positive; other times negative or non-existent) from one set of empirical measures of religiosity to another or from one study population to another (Ellison and Burdette 2012;Jung 2019;Pargament 2002;Schieman 2008;Schieman et al 2005;Pascoe et al 2016;Speed and Fowler 2017;Clements 2014). Based on these inconsistencies, the current literature suggests that the sociological imagination of actors' SOC along with their submission to sociality, especially to deity as its religious kind, is doubtful.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the literature is loaded with agnosticism. It has shown that effects of religiosity on SOC are varying (i.e., sometimes positive; other times negative or non-existent) from one set of empirical measures of religiosity to another or from one study population to another (Ellison and Burdette 2012;Jung 2019;Pargament 2002;Schieman 2008;Schieman et al 2005;Pascoe et al 2016;Speed and Fowler 2017;Clements 2014). Based on these inconsistencies, the current literature suggests that the sociological imagination of actors' SOC along with their submission to sociality, especially to deity as its religious kind, is doubtful.…”
Section: Introductionmentioning
confidence: 99%